Factors Associated with Hypertension Patient Compliance Implementing the COVID-19 Health Protocol - Ranti Marisa; Gamya Tri Utami; Wan Nishfa Dewi (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2022)
COVID-19 is a disease that infects the respiratory tract to the deepest tip of the lungs. Most of the COVID-19 patients have comorbidities with hypertension, especially in the elderly. Increasing age coupled with pre-existing diseases make the elderly more susceptible to more severe COVID-19 infections. This study aims to determine what factors are related to the compliance of hypertension patients in implementing the COVID-19 health protocol. This study uses a descriptive correlation design and uses cross sectional approach. The research sample was 70 respondents who were taken based on the inclusion criteria using purposive sampling technique. The measuring instrument used is a questionnaire sheet for the variables of knowledge, attitudes, family support, and COVID-19 health protocol compliance. The analysis used is univariate analysis and bivariate analysis using chi-square test. After collecting data on 70 respondents with hypertension at one of the public health center in Pekanbaru, the results of the chi-square test on the attitude variable with compliance showed p value 0.036 < (0.05), the family support variable with compliance obtained p value 0.005 < (0.05), and the knowledge variable obtained p value 0.212 > (0.05). Based on the results of statistical tests, it can be concluded that there is a correlation between attitude factors and family support factors with hypertension patient compliance in implementing health protocols, while there is no correlation between knowledge factors and hypertension patient compliance in implementing health protocols